2019
DOI: 10.1002/ece3.5814
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of land‐use changes on herbivory and pollination networks

Abstract: Land‐use changes, one of the greatest threats to global biodiversity, can cause underappreciated effects on ecosystems by altering the structures of interspecific interaction networks. These effects have typically been explored by evaluating interaction networks composed of a single type of interaction. Therefore, it remains unclear whether the different types of interaction networks sharing the same species respond to the same land‐use changes in a similar manner.To compare the responses of herbivory and poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 59 publications
(138 reference statements)
1
11
0
Order By: Relevance
“…Therefore, in light of the unutilized plant species hypothesis, we may explain the varying correlation between plant and insect diversities among previous studies by examining such factors. Second, previous studies have suggested that the proportion of generalist insects varies among study systems that differ in time after disturbance (Piechnik, Lawler, & Martinez, 2008), degree of land‐use intensification (de Araújo, Vieira, Lewinsohn, & Almeida‐Neto, 2015; Shinohara, Uchida, & Yoshida, 2019), spatial scale (Hughes, 2000) and taxonomic groups (Forister et al, 2015). Therefore, incorporating these factors into future studies would help explain the relationship between plant and insect species richness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in light of the unutilized plant species hypothesis, we may explain the varying correlation between plant and insect diversities among previous studies by examining such factors. Second, previous studies have suggested that the proportion of generalist insects varies among study systems that differ in time after disturbance (Piechnik, Lawler, & Martinez, 2008), degree of land‐use intensification (de Araújo, Vieira, Lewinsohn, & Almeida‐Neto, 2015; Shinohara, Uchida, & Yoshida, 2019), spatial scale (Hughes, 2000) and taxonomic groups (Forister et al, 2015). Therefore, incorporating these factors into future studies would help explain the relationship between plant and insect species richness.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the correlation between plant and herbivorous insect species richness was negatively affected by insect generality, which indicates that the possibility of colonization of specialist insect species was enhanced with increasing plant species richness, whereas generalist insect species occurred irrespective of plant species richness. It has been suggested that insect generality may vary among study systems that differ in time after disturbance (Piechnik et al 2008), degree of land-use intensification (de Araujo et al 2015, Shinohara et al 2019, spatial scale (Hughes 2000), and taxonomical groups (Forister et al 2015). Therefore, incorporating those factors in future studies may help explain the relationship between plant-insect species richness.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that the correlation between plant and herbivorous insect species richness was negatively affected by insect generality, which indicates that the possibility of colonization of specialist insect species was enhanced with increasing plant species richness, whereas generalist insect species occurred irrespective of plant species richness. It has been suggested that insect generality may vary among study systems that differ in time after disturbance (Piechnik et al 2008), degree of land-use intensification (de Araujo et al 2015, Shinohara et al 2019), spatial scale (Hughes 2000), and taxonomical groups (Forister et al 2015). Therefore, incorporating those factors in future studies may help explain the relationship between plant–insect species richness.…”
Section: Discussionmentioning
confidence: 99%
“…herbivory and pollination) in hybrid network communities. However, the role of stage structure has been largely ignored in community network studies (Melián et al 2009, Allesina and Tang 2012, Bascompte and Jordano 2014, Suweis et al 2014, Shinohara et al 2019, Valdovinos 2019. Systematic measurements of structural properties (e.g.…”
Section: The Way Forwardmentioning
confidence: 99%